Guidance statement on BRCA1/2 tumor testing in ovarian cancer patients - Capoluongo, Ettore; Schirmacher, Peter; Endris, Volker (Seminars in oncology, 2017)
The approval, in 2015, of the first poly (adenosine diphosphate-ribose) polymerase inhibitor (PARPi; olaparib, Lynparza) for platinum-sensitive relapsed high-grade ovarian cancer with either germline or somatic BRCA1/2 deleterious mutations is changing the way that BRCA1/2 testing services are offered to patients with ovarian cancer. Ovarian cancer patients are now being referred for BRCA1/2 genetic testing for treatment decisions, in addition to familial risk estimation, and irrespective of a family history of breast or ovarian cancer. Furthermore, testing of tumor samples to identify the estimated 3%-9% of patients with somatic BRCA1/2 mutations who, in addition to germline carriers, could benefit from PARPi therapy is also now being considered. This new testing paradigm poses some challenges, in particular the technical and analytical difficulties of analyzing chemically challenged DNA derived from formalin-fixed, paraffin-embedded specimens. The current manuscript reviews some of these challenges and technical recommendations to consider when undertaking BRCA1/2 testing in tumor tissue samples to detect both germline and somatic BRCA1/2 mutations. Also provided are considerations for incorporating genetic analysis of ovarian tumor samples into the patient pathway and ethical requirements.